Myocarditis Mimicking ST-Elevation Myocardial Infarction: A Case Report - Dabbouss, Mohammed; Chalhoub, Mariam; El Orra, Said; Saba, Michel; Ardo, Charbel (International Journal of Clinical Research, 2024)
Background: Myocarditis is the inflammation of the heart muscle, which affects mostly the young population. Patients may experience symptoms ranging from chest pain, fatigue, dyspnea, to more serious conditions such as heart failure and arrhythmias. Diagnosis of myocarditis may be quite confusing as it may mimic myocardial infarction, particularly when ST-elevation is present on electrocardiogram (ECG). Here, we present a challenging presentation of myocarditis mimicking ST-segment elevation myocardial infarction (STEMI). Case Report: A 54-year-old man admitted to the emergency department due to severe chest pain of two hours duration. Lab tests revealed high levels of troponin and D-dimer. ECG revealed tachycardia and ST-elevation in the anterolateral leads, making the diagnosis towards STEMI very likely. However, coronary angiogram didn’t show any obstruction in the right or left coronary arteries. Cardiac magnetic resonance (CMR) imaging was then performed and showed evidence of myocarditis. The patient was treated with colchicine and beta-blocker in which he showed a gradual recovery. Conclusion: Our case highlights the difficulties that a physician may encounter when it comes to diagnosing a case of myocarditis. It should always be kept in mind when dealing with patients presenting with chest pain and ST-elevation, as it may mimic a typical STEMI presentation. A thorough clinical evaluation and the choice of appropriate diagnostic tools are key to the diagnosis of such challenging cases.